Análise da relação entre alavancagem e rentabilidade dos bancos brasileiros listados na Bolsa de Valores de São Paulo, no período de 2001 a 2010 - Mantovani, Marli Helena Colangelo (2012)
The banking sector has prominent position in the economy, dealing with financial resources, providing innovative solutions and mainly by the constant pursuit of increase profitability. There are many reasons for greater profitability of banks, as the high competition in the sector and the pressures of managers for higher returns through riskier operations. Although there are some academic studies on capital structure and profitability of banks, the explanation of leverage and its relationship with banks profitability is still an open question. This paper explores the empirical relevance of the relationship between leverage and profitability of Brazilian banks. It is an empirical research, which seeks to raise exploratory directions, pointing out degrees of correlations, measured by estimation with panel data. The results of this work, based on sample of Brazilian banks listed on the Bolsa de Valores de São Paulo, showed significant relationships between indicators of leverage and profitability indicators. Some considerations are suggested to justify the results achieved, as the increased volumes in funding costs in relation to the total equity ratio and the Capital Adequacy Ratio, that have influenced in a positive way the income on equity